Diagnostic pitfalls: soft-tissue sarcomas initially misdiagnosed as benign vascular anomalies—a case report and systematic review - Styczewska, Malgorzata; Lyzinska, Weronika; Wardecki, Stanislaw Maria; Zajaczkowska, Joanna; Kunc, Michal; Mikaszewski, Boguslaw; Maciag, Rafal; Regent, Bartosz; Wyrzykowski, Dariusz; Jankowska, Anna; Swieton, Dominik; Sinacka, Katarzyna; et al. (Oncology Reviews, 2025)
IntroductionVascular anomalies (VAs), comprising vascular tumors and malformations, are commonly diagnosed based solely on clinical evaluation and imaging. Soft-tissue sarcomas (STSs) may mimic VAs clinically and radiologically, leading to misdiagnosis, delayed treatment, and suboptimal outcomes. In this systematic review, we aimed to summarize patients with a pathological diagnosis of STSs who were initially misdiagnosed with benign VAs, highlighting diagnostic pitfalls.Materials and methodsIn this systematic review (PROSPERO ID: CRD42024615285), we followed the PRISMA 2020 guidelines. The inclusion criteria comprised patients with histologically confirmed STSs who had been initially misdiagnosed as benign VAs based on clinical or radiological features. Literature from five databases was reviewed without language or date restrictions. One additional case of alveolar soft-part sarcoma initially misdiagnosed and mistreated as an arteriovenous malformation from the authors’ institution was added to the analysis.ResultsThe systematic search yielded a total of 96 patients with STS initially misdiagnosed as benign VAs (95 from 77 publications and one from our own case). The median age at presentation was 6 months (range: newborn–88 years). The most frequent symptom was a swelling or mass (75%). In most cases, the misdiagnosis was both clinical and radiological. The median diagnostic delay was 5.5 months. Fifty-nine (61.5%) patients received treatment for the misdiagnosed benign VA, including local interventions (51.0%) and systemic therapies (17.7%). The most commonly misdiagnosed STS subtypes were infantile fibrosarcoma, alveolar soft-part sarcoma, rhabdomyosarcoma, dermatofibrosarcoma protuberans, angiosarcoma, and Ewing sarcoma.ConclusionSeveral STS subtypes may mimic benign VAs clinically and radiologically. The misuse of outdated terminology and limited awareness among clinicians contribute to diagnostic delays. To avoid misdiagnoses, the care for patients with benign VAs should be provided by specialists familiar with the classification and natural history of these lesions. In patients diagnosed with benign VAs based on clinical or imaging features only, all findings should clearly support the diagnosis. Any ambiguity warrants prompt referral to a tertiary center. A biopsy should be considered in doubtful or atypical cases.